2006
DOI: 10.2116/analsci.22.673
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate-selective Electrode Based on a Complex of Copper

Abstract: Sulfate is a major anion with relevance to industrial chemistry, environmental chemistry including pollution studies, biochemistry and mineralogy, as well as several other areas. The fact that sulfur in several other forms is ultimately determined after conversion to sulfate further enhances the importance of sulfate determination. Acid rain is a very serious problem closely connected with the fast development of industries and economics in the world. In order to clarify and evaluate the effect of acid rain on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…When the nitrite ion catalyzes this reaction, the oxidation of CR is much faster, resulting in a considerable discoloration of mixture (Figure 1). For the oxidation of organic compounds (OC), the following reactions can describe the role of nitrite as a catalyst in the presence of bromate [36] After scanning the spectrum of CR in acid medium, in the wavelength range 450-650 nm, the wavelength of maximum absorbance attributed to CR was found to be λ max = 570 nm.…”
Section: Resultsmentioning
confidence: 99%
“…When the nitrite ion catalyzes this reaction, the oxidation of CR is much faster, resulting in a considerable discoloration of mixture (Figure 1). For the oxidation of organic compounds (OC), the following reactions can describe the role of nitrite as a catalyst in the presence of bromate [36] After scanning the spectrum of CR in acid medium, in the wavelength range 450-650 nm, the wavelength of maximum absorbance attributed to CR was found to be λ max = 570 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Zeolites X, Y and 13X were also investigated for the determination of Cu 2? ion [33][34][35][36][37]. Walcarius showed that between ZMCPE and zeolite monograin layers coated on GCE, the former presented a better current response to Cu 2?…”
Section: Sensor Calibrationmentioning
confidence: 99%
“…Nanomaterialh as attracted much attention because of their differenta nd superior properties compared to the bulk phase.E lectronic and optical properties of nanomaterial led to their usage in the field of photocatalysis,p hotovoltaic, sensing, and photonicc rystals [1][2][3][4][5][6].T itanium is the ninth most plenty of element in the Earthsc rust. TiO 2 ,acompound of titanium, is used in many applications from photocatalyst, self-cleaning coatings,a nd paints to solar cells and anticorrosion [7][8][9][10].O ne-dimensional nanostructures such as TiO 2 nanowires,n anorods, nanotubes,n anofiber and their composites with TiO 2 nanoparticles have been reviewed to improve the electron mobility and transport rate [11,12].T iO 2 nanoparticles have superp erformancea nd broada pplications as ap hotocatalyst and catalyst, in solar cells,g as sensors,p igments and other devices [13].D ue to the great oxidizing power, high electro stability,r edox selectivity and easy synthesis of TiO 2 ,i ti sv astly used in electrocatalytic applications [14][15][16][17].T he electrochemical behavior of TiO 2 depends on the crystal structure, surface properties and textural properties such as specific surface area, size,v olumea nd distribution. Many attempts have been created to synthesize TiO 2 with ac ontrollable morphology and facet of structure [18,19].T iO 2 nanoparticles have been combined with other compounds such as graphite and carbonn anotubes to make nanocomposite in the electrochemical analysis in order to determine some of biological compounds [ 20,21] TiO 2 nanomaterials include nanoparticles,n anotubes, nanofibers or theirc omposites can be prepared by many different methods [ 22].A mong these methods, it seems that electrospinning provides the simplest approach to form nanofibers,m icrofibers,n anowires,a nd other nanostructures for different applications.A dvantages of electrospinning method are as follows:1 )L arge specific surface area and pore dispensationo fe lectrospun nanofibers 2) this method is suitable for produce nanostructures an industriall evel, and 3) it is as imple and multifunctional method to formu ltrathin fibers under the influence of an electrostatic field [23-25].T he diametero ft he electrospun nanofibers can be easilyc ontrolled in the range of less than tens of nanometers,w hich is still ab ig problem for other methods.T he electrospinning uses asingle capillarya st he spinneret, which is only appropriate to generate with one particular composition …”
Section: Introductionmentioning
confidence: 99%